On the discontinuous nature of the Mozambique Current - Johann Lutjeharms (South African Journal of Science, 2012)
The concept of a spatially continuous western boundary current in the Mozambique Channel has historically been based on erroneous interpretations of ships' drift. Recent observations have demonstrated that the circulation in the Channel is instead dominated by anti-cyclonic eddies drifting poleward. It has therefore been suggested that no coherent Mozambique Current exists at any time. However, satellite and other observations indicate that a continuous current - not necessarily an inherent part of Mozambique Eddies - may at times be found along the full Mozambican shelf break. Using a high-resolution, numerical model we have demonstrated how such a feature may come about. In the model, a continuous current is a highly irregularly occurring event, occurring about once per year, with an average duration of only 9 days and with a vertical extent of about 800 m. Surface speeds may vary from 0.5 m/s to 1.5 m/s and the volume flux involved is about 10 Sv. The continuous current may occasionally be important for the transport of biota along the continental shelf and slope.